2013
DOI: 10.1145/2390191.2390205
|View full text |Cite
|
Sign up to set email alerts
|

Using implications to choose tests through suspect fault identification

Abstract: As circuits continue to scale to smaller feature sizes, wearout and latent defects are expected to cause an increasing number of errors in the field. Online error detection techniques, including logic implication-based checker hardware, are capable of detecting at least some of these errors as they occur. However, recovery may be expensive, and the underlying problem may lead to multiple failures of a core over time. In this article, we will investigate the diagnostic capability of logic implications to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The error monitoring circuit could be based on a number of runtime error detection approaches (e.g. logic implications [35]- [37], parity check codes [38], [39] selective duplication [40], etc). Table II. For this example, we assume that the error monitoring circuit is in place in the original ASIC layer and is able to trigger the dynamic reconfiguration of the FPGA layer for proper repair.…”
Section: Architecture and Multiplier Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…The error monitoring circuit could be based on a number of runtime error detection approaches (e.g. logic implications [35]- [37], parity check codes [38], [39] selective duplication [40], etc). Table II. For this example, we assume that the error monitoring circuit is in place in the original ASIC layer and is able to trigger the dynamic reconfiguration of the FPGA layer for proper repair.…”
Section: Architecture and Multiplier Repairmentioning
confidence: 99%
“…While, the exact nature of the diagnosis approach in a 3D IC stack is outside the scope of this article and a subject of our future investigations, our previous work [35]- [37] on online error detection in a 2D IC could be adapted to identify the location of some defective behavior in a 3D stack. For example, we have previously demonstrated that when logic implications are used for online-error detection, determining which implication was violated provides automatic diagnostic data because each implication can only protect a well-defined subset of all possible circuit sites [37].…”
Section: Diagnosis and Test Of Failing Partitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach uses logic implications [Dworak et al 2012] and well-established implication-based techniques [Bushnell and Agrawal 2000]. In this method, logic implications define the expected relationships between values at different circuit sites.…”
Section: Related Workmentioning
confidence: 99%